2005
DOI: 10.1111/j.1651-2227.2005.tb01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an individualized written home‐management plan in the control of moderate persistent asthma: A randomized, controlled trial

Abstract: Background: The management of childhood asthma necessitates a comprehensive approach including pharmacological treatment as well as education about self‐evaluation and home management of the condition. Aim: To evaluate the efficacy of adding an individualized written home‐management plan in the control of moderate persistent asthma. Methods: Children with moderate persistent asthma were randomized to receive either an individualized written home‐management plan or no plan, in addition to standard asthma therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
0
22
1
1
Order By: Relevance
“…For the purposes of analysis, this yielded a total of 5 distinct comparator arms (or between-group comparisons) examining 2 types of action plan. With regard to testing the efficacy of a written action plan over none, only 1 full-text publication trial involving 68 schoolaged children was identified 25 (Figure 1). Table 1 summarizes the methodological quality of the included studies, all of which were parallel-group designs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of analysis, this yielded a total of 5 distinct comparator arms (or between-group comparisons) examining 2 types of action plan. With regard to testing the efficacy of a written action plan over none, only 1 full-text publication trial involving 68 schoolaged children was identified 25 (Figure 1). Table 1 summarizes the methodological quality of the included studies, all of which were parallel-group designs.…”
Section: Resultsmentioning
confidence: 99%
“…Agrawal et al, 25 10 includes an extra zone between zones 1 and 2 for the symptom-based written action plan and a zone between zones 2 and 3 for both written action plans. less than 2-hour relief with a bronchodilator, and/or severe symptoms).…”
Section: Written Plan Vs Nonementioning
confidence: 99%
See 1 more Smart Citation
“…Although data are limited on whether having an asthma care plan is superior to none (24), a randomized, controlled trial documented that having a care plan was associated with significantly fewer asthma exacerbations, fewer missed school days, lower symptom scores, and less nocturnal awakening (25). Written asthma care plans also are associated with reduced odds of asthma ED visits and hospitalizations in children (26), and 90% of urban parents in one study cited asthma care plans as useful in managing children's asthma exacerbations (27).…”
Section: Discussionmentioning
confidence: 98%
“…Auch muss der Patient in der richtigen Behandlungsdurchführung geschult werden. Zu diesem Zweck kommen evidenzbasierte Schulungsprogramme, die auf die Altersgruppe der Kinder und Jugendlichen abgestimmt sind, zum Einsatz [28,29,30,31]. Ergänzt wird das medizinische Rehabilitationsangebot durch entsprechende Sport-und Physiotherapiemaßnahmen, um die körperliche Leistungsfähigkeit zu steigern und dadurch langfristig wieder eine Medikamentenreduktion zu erreichen [32,33].…”
Section: Asthma Bronchialeunclassified